Pengembangan Motorik Halus Anak Usia Dini melalui Kegiatan Melukis di TK PKK Prajegan Sukorejo Ponorogo - Siti Rofichoh; Abdah Munfaridatus Sholihah; Suci Midsyahri Azizah (Social Science Academic, 2025)
Motor development is very important for early childhood growth and development. Motor development is divided into 2, namely fine motor and gross motor. Fine motor usually uses small muscles and gross motor uses large muscles. Activities that can hone fine motor skills such as writing, scissors, coloring and sticking. Painting is an activity that uses canvas but instead uses thin sponges, liquid dyes, brushes and palettes. At the end of the school introduction period, PKK Prajegan Kindergarten held a painting activity to hone the ability to combine hand and eye movements. In this study, observation and documentation are used. This activity was carried out by approximately 30 children from group A and group B. children were very enthusiastic in this activity. The purpose of this painting activity is to train concentration in hand and eye movements, practice patience, social-emotional and get to know the surrounding environment. It can also be a memory for children when they are adults.